A legal vision of violence and perspective of change, from the theory of attachment - Ludeña González, Gerardo Francisco (2020)
Attachment theory constitutes one of the psychological phenomena that, based on affective ties and the way it is shown, will evidently generate a conditioning and parental relationship from childhood that affects social coexistence. Hence, on multiple occasions, if the relationship has not been positive, different types of relationships are generated. Bowlby was the forerunner of this attachment theory, potentially so influential with emotions. For the legal world, violence is punished with penalties that are increasingly severe and draconian, however, many of these criminal activities accompanied by violence are generated by minors, hence the need for protection policies for children and adolescents with respect to their origin of violence because the family as a basic identity card of society has internal and external forces that influence the formation of the state it represents. Historically the family maintains and precedes the rule of law. A democratic state has the duty and obligation to preserve that internal order, promoting universal values, about beliefs, religions and philosophies. We ask ourselves: Is the family an effective institution for the fight against corruption? Thus, the family fulfills a transcendental role because it is the first school of values and morals that will be part of the ethics and actions of the individual in the future. For this reason, we rescue the importance of the family for the human person as a subject of law and the effect that this will have when forming part of a just society, away from corruption, as happens in countries where the crime rate has decreased.